Characteristics of Homogeneous-Heterogeneous Reactions and Melting Heat Transfer in the Stagnation Point flow of Jeffrey Fluid - T. Hayat; Muhammad Farooq; Ahmed Alsaedi (Journal of Applied Fluid Mechanics, 2016)
This work focuses on melting heat transfer in the stagnation point flow of Jeffrey fluid past an impermeable stretching cylinder with homogeneous-heterogeneous reactions. Characteristics of magnetohydrodynamic flow are explored in presence of heat generation/absorption. Diffusion coefficients of species A and B are taken of the same size. Heat released during chemical reaction is negligible. A system of ordinary differential equations is obtained by using suitable transformations. Convergent series solutions are derived. Impacts of various pertinent parameters on the velocity, temperature and concentration distributions are discussed. Numerical values of skin friction coefficient and Nusselt number are computed and analyzed. Present results are compared with the previous published data.